2016
DOI: 10.1161/atvbaha.115.306563
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Disarray as a Mechanism for Greater Abdominal Versus Thoracic Aortic Stiffness With Aging in Primates

Abstract: Objective Increased vascular stiffness is central to the pathophysiology of aging, hypertension, diabetes and atherosclerosis. However, relatively few studies have examined vascular stiffness in both the thoracic and abdominal aorta with aging, despite major differences in anatomy, embryological origin and relation to aortic aneurysm. Approach and Results The two other unique features of this study were 1) to study young (9±1 years) and old (26±1 years) male monkeys, and 2) to study direct and continuous mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 45 publications
2
57
1
Order By: Relevance
“…While it remains controversial as to whether increased arterial stiffness precedes or is a consequence of pathologies such as atherosclerosis, 24 a recent study demonstrated that segmental aortic stiffening, and the resultant aortic stiffness gradients, may trigger aortic remodeling leading to abdominal aortic aneurysm (AAA) formation. 25 Complementing these findings, research by Zhang et al conducted in non-human primates indicates that the abdominal segment of aged aortae exhibits the highest regional stiffness 26 – thus making the abdominal aorta a predilection site for aneurysm formation. Furthermore, aortic stiffness is elevated in various connective tissue diseases, including Marfan syndrome, that predispose patients to progressive aortic dilatation, potentially resulting in fatal aortic dissection and death.…”
Section: Clinical Significance Of Arterial Stiffnessmentioning
confidence: 86%
See 1 more Smart Citation
“…While it remains controversial as to whether increased arterial stiffness precedes or is a consequence of pathologies such as atherosclerosis, 24 a recent study demonstrated that segmental aortic stiffening, and the resultant aortic stiffness gradients, may trigger aortic remodeling leading to abdominal aortic aneurysm (AAA) formation. 25 Complementing these findings, research by Zhang et al conducted in non-human primates indicates that the abdominal segment of aged aortae exhibits the highest regional stiffness 26 – thus making the abdominal aorta a predilection site for aneurysm formation. Furthermore, aortic stiffness is elevated in various connective tissue diseases, including Marfan syndrome, that predispose patients to progressive aortic dilatation, potentially resulting in fatal aortic dissection and death.…”
Section: Clinical Significance Of Arterial Stiffnessmentioning
confidence: 86%
“…The study by Zhang, et al published in ATVB clearly demonstrated that aortic stiffness increases with age; however, the most severe increases in aortic stiffness were observed in the abdominal aorta, where values in young monkeys equaled or exceeded values of thoracic aortic stiffness in old monkeys. 26 Altogether, these results suggest that regional differences exist between the abdominal and thoracic regions of the aorta that ultimately differentially impact arterial stiffness.…”
Section: Underlying Mechanisms Of Arterial Stiffeningmentioning
confidence: 87%
“…This observation is not entirely novel since conflicting trends in aortic scleroprotein contents have long been noted, indicating that other extracellular matrix proteins, cross-linking, glycation, and structural or architectural rearrangement may contribute to altering the mechanical properties of the vascular wall [43]. It was recently shown that scleroprotein disarray as opposed to elastin/collagen ratio changes accounted for the increase in abdominal aortic stiffness versus thoracic stiffness in aged primates [33]. In this study, the authors demonstrated that, as in our salt model, elastin disarrays were more pronounced at the abdominal site and thus may account for the observed increased in stiffness.…”
Section: Discussionmentioning
confidence: 95%
“…The aorta is often considered as a single entity; however, arterial stiffening develops differently along the aortic bed with aging in both humans and animal models [31-33]. This may be due to the fact that the thoracic and abdominal aorta have different embryologic origins, different means of maturation, and different structural and mechanical properties [34, 35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation